KARAKTERISTIK PENYIMPAN KALOR LATEN PADA PARABOLIC MIRROR DISH - Agus Dwi Korawan (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2023)
Storing heat in the form of latent heat is a good method, because it is able to store a large amount of heat energy with a small volume of storage media. The use of paraffin as a heat storage medium has many advantages, including thermal stability, non-toxicity, no degradation, and high latent heat storage capacity. This study uses a parabolic mirror dish as a collector of solar thermal energy, equipped with a hinged holder that can be adjusted so that it points to the sun's position from morning to evening, the collected energy is stored in thermal storage using paraffin as a storage medium. The research was conducted from 09.00 WIB to 24.00 WIB, the research location was on the Ronggolawe College of Technology campus. The results showed that the highest temperature obtained in paraffin as a heat storage was 112 oC, while the duration of storing until 24.00 WIB was still able to maintain the temperature at 36 oC.